Niniak Mamak's Permission in Minangkabau Community Marriage Perspective of 'Urf (Case Study in Kenagarian Panampuang, West Sumatra) - Siregar, Ihram Ahmed; Amar, Riski; Yuni, Safira (PERADA, 2024)
The permission of niniak mamak as a condition of marriage in Minangkabau society is one of the customary rules that must be carried out before a marriage takes place, even though it is not regulated by Islamic law or state law. Departing from this, this research aims to explore the reasons for this customary rule and analyze its relevance to Islamic law. This research is qualitative by conducting a field study. Data collection uses interview, observation and documentary techniques and uses 'urf as an analytical. This article finds, first, the rule of niniak mamak permission as a condition of marriage is a customary rule that has been carried out for generations, besides that, this rule is also a place for silahturahmi the mamak of both parties and this rule aims to protect the children of the kemenakan and avoid unwanted things in the future. Secondly, from the perspective of 'urf, the permission of the niniak mamak in the marriage of the Minangkabau people is included in the 'urf shahih because this rule is to maintain the benefit of the children and does not violate the Shari'at.